A synonymic catalog of the Neotropical Crabronidae and Sphecidae (Hymenoptera: Apoidea) - Amarante, Sérvio Túlio P. (Arquivos de Zoologia, 2002)
A synonymyc catalogue for the species of Neotropical Crabronidae and Sphecidae is presented, including all synonyms, geographical distribution and pertinent references. The catalogue includes 152 genera and 1834 species (1640 spp. in Crabronidae, 194 spp. in Sphecidae), plus 190 species recorded from Nearctic Mexico (168 spp. in Crabronidae, 22 spp. in Sphecidae). The former Sphecidae (sensu Menke, 1997 and auct.) is divided in two families: Crabronidae (Astatinae, Bembicinae, Crabroninae, Pemphredoninae and Philanthinae) and Sphecidae (Ampulicinae and Sphecinae). The following subspecies are elevated to species: Podium aureosericeum Kohl, 1902; Podium bugabense Cameron, 1888. New names are proposed for the following junior homonyms: Cerceris modica new name for Cerceris modesta Smith, 1873, non Smith, 1856; Liris formosus new name for Liris bellus Rohwer, 1911, non Lepeletier, 1845; Liris inca new name for Liris peruanus Brèthes, 1926 non Brèthes, 1924; and Trypoxylon guassu new name for Trypoxylon majus Richards, 1934 non Trypoxylon figulus var. majus Kohl, 1883.